(untitled) (Eternitas: Jurnal Teknik Sipil, 2025)
This study aims to analyze the annual water balance and develop a water allocation plan for the Manikin Watershed (DAS Manikin) located in Kupang Regency, East Nusa Tenggara Province (NTT), Indonesia. The primary motivation for this research is the imbalance between water availability and demand, particularly during the dry season. The methodology includes the collection of climate and infrastructure data, analysis of water demand and availability, and water balance modeling using Excel and Cropwat 8 software. Reliable discharge was calculated using the FJ Mock method with an 80% probability (Q80%). The analysis revealed that the peak irrigation water demand occurs in August, reaching 0.54 l/s/ha, while the available discharge in the same month is only 0.67 m³/s, indicating a significant water deficit. This study offers technical and policy recommendations for efficient, equitable, and sustainable water management in semi-arid regions vulnerable to drought. Keywords: water balance, irrigation demand, reliable discharge, Manikin Watershed, water allocation